Anatomical aspects of the selective infraspinatus muscle neurotization by spinal accessory nerve. Issue 4 (2nd August 2021) - Kaiser, Radek; Krajcová, Aneta; Makel, Michal; Ullas, Gautham; Němcová, Veronika
Abstract: The suprascapular nerve (SSN) is commonly reconstructed by spinal accessory nerve (SAN) transfer. However, reinnervation of its branch to the infraspinatus muscle (IB-SSN) is poor. Reconstruction of the SSN in cases of scapular fractures is frequently neglected in clinical practice. The morphological study was performed on 25 adult human cadavers. The course and the length of SSN of minimal diameter of 2 mm within the trapezius muscle, the length of the distal stump of IB-SSN to its branching point and the length of the SSN available for reconstructive procedure were measured. The feasibility study of the SAN - IB-SSN neurotization performed by using a bony canal under the spine of scapula was performed. The mean distance of the SAN from the spine was 8.5 cm (±0.88) at the point where it perforates the trapezius muscle and 4.49 cm (±0.72) at the most distal part of the nerve. The mean length of the intramuscular portion of the nerve was 14.74 cm (±1.99). It ran under a mean latero-medial angle of 15.54 ° (±2.51). The mean distance between the medial end of the scapular spine and the SAN was 2.44 cm (± 0.64). The mean length of the IB-SSN was 3.6 cm (± 0.67). The mean length of the SAN stump which was mobilized from its original course and transferred to the infraspinous fossa to reach distal stump of the IB-SSN was 8.09 cm (±1.6). Direct SAN to IB-SSN transfer is anatomically feasible in the adult population.